REDUKSI HARMONISA PADA UNINTERRUPTIBLE POWER SUPPLY (UPS) DENGAN SINGLE TUNED PASSIVE FILTER - Agus Almi (Universitas Harapan Medan, 2019)
Using non-linear load in UPS (Uninterruptible Power Supply) can cause harmonic distortion which will eventually have the effect on power quality. The research was designed as a single-turned passive filter to cope with harmonic distortion in UPS. In this phase, THDv, THDi, and IHDi were measured in UPS. MATLAB/Simulink was used for simulation of filter testing. After Single Turned Passive Filter was installed, the third order of harmonic current decreased from 47.69% to 7.08% or reduced 40.61%